Membangun Hubungan Sosial Kemasyarakatan Ideal di Era Informatika: Perspektif Al-Qur'an - Sukaenah; Abdul Haris Tambunan; Nur Ainy; Hamdan Muafi (Universitas Islam Tribakti Lirboyo Kediri, 2023)
This article explores the important task of building ideal social and community relations in the information age, guided by the Qur'anic perspective. The study aims to outline the principles embedded in the Qur'anic teachings that can facilitate the establishment of harmonious and ethical social relations amidst the ever-evolving landscape of information technology. Using a comprehensive research methodology, the study meticulously examines and extracts insights from various relevant literature sources. The findings of this study emphasize the identification of key principles that are essential for building an ideal social framework in the age of informatics. These principles, rooted in the Qur'an, involve the concepts of justice, mercy (ikhsan), unity, brotherhood, maintenance of friendship, avoidance of prejudice, and observance of the principle of tabayyun. As a guide to fostering balanced and ethical interactions, these principles make a significant contribution to the development of an understanding of Qur'anic values in the context of the information society. This journal article not only presents a theoretical framework for building ideal social relationships, but also offers practical insights for individuals facing the challenges posed by information technology. By emphasizing the relevance of Qur'Änic principles in contemporary social dynamics, this research aims to contribute to a deeper understanding of the fusion between religious teachings and the digital age, with the hope of promoting a more enlightened and morally grounded approach to social interaction in the informatics era.